Seasonal history, plant interactions and egg parasitism of the variegated caper bug Stenozygum coloratum Klug (Heteroptera: Pentatomidae). (27th June 2015) - Samra, Shahar; Ghanim, Murad; Protasov, Alex; Mendel, Zvi
Abstract: The variegated caper bug Stenozygum coloratum Klug is common in the Middle East, where it is a minor agricultural pest. Recently, it was found that S. coloratum is an alternative host for the egg parasitoid Ooencyrtus pityocampae Mercet, an important natural enemy of the pine processionary moth Thaumetopoea wilkinsoni Tams, a major pest of pines. This discovery, coupled with the general lack of knowledge of S. coloratum, prompted the present study, which focused on seasonal activity of S. coloratum in Israeli pine forests, bidirectional interactions between the bug and its host the caper plant Capparis spp ., and parasitism of its eggs. Stenozygum coloratum activity lasted mainly from May to October, and was followed by an adult winter diapause. Individuals formed large aggregations, causing early withering of plants and a shortening their annual growth periods. Reproductive activity peaked in August and ended in September. Egg parasitism rates increased throughout this period. Several Ooencyrtus spp., including known natural enemies of various pests, parasitized the eggs of S. coloratum and other associated pentatomids found on the caper plants. Thus, capers probably serve as a refuge for these potentially important egg parasitoids. The potential of caper plants and their fauna for biological control programmes is discussed.